1986
DOI: 10.1007/bf02346059
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces rimosus extracellular proteases 3. Isolation and characterization of leucine aminopeptidase

Abstract: Summary.A leucine aminopeptidase was purified to homogeneity from Streptomyces rimosus culture filtrates, which are waste broth of oxytetracycline bioproduction process. Purification procedure includes ultrafiltration and chromatography on CM-Sephadex, AH-Sepharose and FPLC Mono S column.The enzyme is a monomer with molecular weight of 27,500 Daltons and pI of 7.3, stable in broad pH range and up to 70°C. It is a metallo enzyme dependent o n C a 2+ ions for its full activity. By its specificity it is a true am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 34 publications
3
12
0
1
Order By: Relevance
“…Kcat for hydrolysis of leu-pNA is 2-3 s-l, and K J K m is 7.7 x lo3. These values are similar to those obtained by Vitale et al (1986) for the S. rimosus LAP.…”
Section: Table 4 Efects Of Inhibitors On S Lividans L a Psupporting
confidence: 90%
See 1 more Smart Citation
“…Kcat for hydrolysis of leu-pNA is 2-3 s-l, and K J K m is 7.7 x lo3. These values are similar to those obtained by Vitale et al (1986) for the S. rimosus LAP.…”
Section: Table 4 Efects Of Inhibitors On S Lividans L a Psupporting
confidence: 90%
“…Nevertheless, S. lividans LAP was inhibited by o-phenanthroline, Na,-EDTA, NTA and EGTA, indicating that it is a metalloproteinase. Furthermore, the enzyme was partially inhibited by bestatin, a known inhibitor of aminopeptidases (Vitale et al, 1986). The combined data indicate that S. lividans LAP is a metallo-enzyme, produced during stationary phase, that has a rather narrow range of substrate specificities.…”
Section: Table 4 Efects Of Inhibitors On S Lividans L a Pmentioning
confidence: 80%
“…Some other aminopeptidase inhibitors containing a 3-amino-2-hydroxy-carboxylic acid also inhibit bacterial aminopeptidases: Wilkes and Prescott (1985) have shown that bestatin and amastatin are slow-and tight-binding competitive inhibitors of leucine aminopeptidase from A. proteolytica. Leucine aminopeptidase from S. rimosus is also inhibited by bestatin and amastatin (Vitale et al 1986), and leucine aminopeptidase from S. lividans is inhibited by bestatin (Aphale and Strohl 1993). All these aminopeptidases belong to the PepA-type metallo-aminopeptidases that appear to be quite common in Streptomyces species (Gonzales and Robert-Baudouy 1996).…”
Section: Discussionmentioning
confidence: 95%
“…Other aminopeptidases used were isolated in our laboratories: extracellular leucine aminopeptidase from S. rimosus (Vitale et al 1986), intracellular arginine aminopeptidase from S. rimosus (Vitale et al 1996), intracellular proline aminopeptidase from S. rimosus (Lj. Vitale, T. Tripić, I. Škrtić, unpublished work), dipeptidyl aminopeptidase III from human erythrocytes (Abramić et al 1988), and aminopeptidase N from egg white (Škrtić and Vitale 1994).…”
Section: Chemicals and Enzymesmentioning
confidence: 99%
See 1 more Smart Citation